Engineering Approaches in Human Gamma Delta T Cells for Cancer Immunotherapy - Fisher, Jonathan; Anderson, John (Frontiers in Immunology, 2018)
Sharing both innate and adaptive immune properties, γδT cells are attractive candidates for cellular engineering. As the cancer immunotherapy field becomes increasingly busy, orthogonal approaches are required to drive advancement. Engineering of alternative effector cell types such as γδT cells represents one such approach. γδT cells can be modified using many of the techniques used in αβT cell engineering, with the added advantage of innate-like tumor recognition and killing. Progress has been made in T-cell receptor transfer to and from γδT cells as well as in a number of chimeric-antigen receptor based strategies. As the cancer immunotherapy field moves beyond repetitive iteration of established constructs to more creative solutions, γδT cells may offer an attractive chassis to drive anti-tumor responses that are not only broader, but also possess a more favourable safety profile.